Medical Parasitology Taxonomy Update, January 2018 to May 2020 - Mathison, Blaine A. (J Clin Microbiol, 2021)
The taxonomy of parasites of medical and public health importance is rapidly evolving. This minireview provides an update of taxonomic revisions and additions in the field of medical parasitology from January 2018 to May 2020. Several established human parasites have been reassigned to different genera over the past 2 years, while a number of novel parasites of humans have been identified. A comprehensive summary of these changes is provided here, and Taenia suihominis is proposed as a replacement name for Taenia asiaticus Eom et al., which is a homonym of Taenia asiatica von Linstow.